Vitamin D Deficiency - New Insights 2023
DOI: 10.5772/intechopen.105820
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Efficacy and Mechanism of Vitamin D in the Treatment of “Kidney-Brain” Disorders

Abstract: Accumulating evidences have shown that serum 25-hydroxyvitamin D concentrations were inversely correlated with the incidence or severity of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and that vitamin D deficiency might be associated with an increased susceptibility to many of the complications accompanied by COVID-19, such as disorders in kidney and brain. Our previous experimental studies demonstrated that vitamin D and its analogs could protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…The baselines of all studies were balanced approximately, see Table 1. Among the 11 included studies, 3 studies [10,12,18] adopted the random number table method for grouping; 2 studies [16,17] took the lottery method; 5 studies [11,14,15,19,20] only mentioned randomness, and 1 study [13] did not mention grouping method. Allocation hiding was not mentioned in all studies.…”
Section: The Basic Characteristics and Quality Evaluation Included In...mentioning
confidence: 99%
See 2 more Smart Citations
“…The baselines of all studies were balanced approximately, see Table 1. Among the 11 included studies, 3 studies [10,12,18] adopted the random number table method for grouping; 2 studies [16,17] took the lottery method; 5 studies [11,14,15,19,20] only mentioned randomness, and 1 study [13] did not mention grouping method. Allocation hiding was not mentioned in all studies.…”
Section: The Basic Characteristics and Quality Evaluation Included In...mentioning
confidence: 99%
“…Allocation hiding was not mentioned in all studies. The blind method was involved in 2 studies, [10,12] while the rest studies [11,[13][14][15][16][17][18][19][20] did not mention it. The results of 1 study [16] were selectively reported, and none of the studies had bias from other sources.…”
Section: The Basic Characteristics and Quality Evaluation Included In...mentioning
confidence: 99%
See 1 more Smart Citation